The Usage of Backscattered Electrons in Scanning Electron Microscopy - Kejzlar, Pavel; Švec, Martin; Macajová, Eva (Manufacturing Technology Journal, 2014)
Secondary and backscaterred electrons are the most common signals used for imaging in the scanning electron microscopy. Generally, SE are used to obtain topographical contrast while BSE show differences in chemical composition (so called Z-contrast).The aim of the present work is to show possibilities and techniques to obtain not-so-common information using BSE, as e.g. orientation contrast, residual stress, different allotropic modifications, etc.
Keywords: Scanning Electron Microscopy; BSE; Structure